The unforeseen during biotechnological therapy for moderate‐to‐severe psoriasis: How to manage pregnancy and breastfeeding, infections from Mycobacterium tuberculosis, hepatitis B virus, hepatitis C virus, and HIV, surgery, vaccinations, diagnosis of malignancy, and dose tapering. Issue 3 (30th April 2020) - Sacchelli, Lidia; Magnano, Michela; Loi, Camilla; Patrizi, Annalisa; Bardazzi, Federico
Abstract: The use of biotechnological therapies for moderate‐to‐severe psoriasis is ever‐expanding and it is becoming increasingly more frequent to encounter different unforeseen events during their use, such as fertile patients becoming pregnant and breastfeeding, development of infections due to personal habits like tuberculosis, hepatitis B virus, hepatitis C virus, or HIV, scheduling of surgical procedures, need of vaccinations, development of malignancy, and evaluation of dose tapering. As any clinician may experience at least one of these unexpected events, it should be good practice to know how to manage them. Thus, a practical analysis has been proposed in this study.